2018
DOI: 10.1177/1359104518805227
|View full text |Cite
|
Sign up to set email alerts
|

Taking the stone from my heart: An exploration of the benefits of a mentoring programme (PROMISE) for children at risk of significant harm

Abstract: This article reports on a multi–methods longitudinal evaluation of the PROMISE mentoring scheme which was developed in Somerset UK to offer a continuing relationship for vulnerable young people with a volunteer mentor. The overall findings indicate that mentoring was experienced very positively and contributed to both fostering a sense of trust and to reducing the insecure attachments of the young people. The findings are considered within a relational and attachment framework to offer a model of how mentoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The findings of the current study are consistent with our previous studies (Dallos, & Carder-Gilbert, 2019), but this current study provides additional themes which indicated that the mentors regarded it as important to respond empathetically to the young person's needs and emotions. It was also interesting that the mentor acknowledged that, like the young person, they valued the shared elements, such as the humour, help and empathic support.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the current study are consistent with our previous studies (Dallos, & Carder-Gilbert, 2019), but this current study provides additional themes which indicated that the mentors regarded it as important to respond empathetically to the young person's needs and emotions. It was also interesting that the mentor acknowledged that, like the young person, they valued the shared elements, such as the humour, help and empathic support.…”
Section: Discussionsupporting
confidence: 91%
“…Dallos and Comley-Ross (2005) found that when absent, mentees felt mentors 'held them in mind', in that they perceived their mentors to still think of them and care for their wellbeing. Dallos and Carder-Gilbert (2019) conducted a longitudinal study which indicated that important to the development of a positive relationship was a process of internalisation of conversations and interactions with their mentors. The young people described that dysregulating intrusions from prior traumatic events became less frequent as the relationship developed.…”
Section: Introductionmentioning
confidence: 99%
“…The recreational component refers to connectedness, companionship, friendship, and ongoing communication [ 80 , 82 , 91 , 92 , 94 , 96 , 97 , 98 , 99 , 103 , 104 ], accompanied by collaboration, mutuality [ 39 , 86 , 94 , 95 , 96 , 103 , 105 ], and self-disclosure [ 106 , 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carder-Gilbert H, Dallos R Plymouth University Vulnerable children and young people have benefited from being mentored by a stable adult; however, little is known about why mentoring is helpful and this limits the extent to which theory or research can help guide its application (Dallos et al, 2018). Co-occupation is a synchronous back and forth of actions (Pierce, 2000).…”
Section: Menteesmentioning
confidence: 99%